Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik tentang Keragaman di Indonesia pada Kelas V SD Inpres Oesapa Kota Kupang - Nauk, Irna Mayangsari; Taneo, Silvester Petrus; Devi, Rista Apriliya (Lembaga Yasin AlSys, 2025)
This research aims to improve student learning outcomes through the application of a problem based learning model about Diversity in Indonesia in class V of SD Inpres Oesapa, Kupang City. This type of research is classroom action research. The data collection techniques used are observation techniques and test techniques; The subjects in the research were 28 students consisting of 14 men and 14 women using data analysis techniques, namely Qualitative Descriptive. This research was carried out at SD Inpres Oesapa, Kupang City, with the results of the research showing that the results in the first cycle of 28 students who achieved completeness were 12 people with a percentage of (43%) while those who did not achieve completeness were 16 people with a percentage of (57.11%) then corrective action was carried out in cycle II and there was a significant increase to 24 people who achieved completeness with a percentage (86%) and 4 people who did not achieve completeness with a percentage (14.28%). Based on the research results above, it can be concluded that the application of the problem based learning (PBL) learning model to improve student learning outcomes about diversity in Indonesia in class V of SD Inpres Oesapa, Kupang City, has been proven to improve student learning outcomes.